Inductive process of moral distress development in viewpoints from surgical nurses: a mixed-method study - Azam Hosseinpour; Fatemeh Keshmiri (BMC, 2024)
Abstract Background Moral distress is a multifactorial and complex phenomenon influenced by various individual, cultural, and systemic factors. This study aimed to investigate the frequency and intensity of nurses' moral distress, explore their experiences, and develop the conceptual model of risk factors of moral distress in surgical units and operating rooms. Method This is a sequential mixed-method study conducted at four teaching hospitals affiliated with the Qom University of Medical Sciences. In the first step, the moral distress of nurses in surgical units and operating rooms was investigated by a survey. The participants included nurses who worked in the operating room and surgical units. (n = 180). The data was collected by a Moral Distress Scale-Revised (MDS-R) questionnaire. In the second step, the experiences of nurses regarding risk factors of moral distress were explored using semi-structured interviews and analyzed using the conventional content analysis by Graneheim and Lundman's approach. Results One hundred eighty nurses participated in this study. The mean total moral distress scores ranged from 12 to 221, with a mean (SD) of 116.8 (42.73). The causes of moral distress cited with the highest frequency and intensity related to the 'role of healthcare providers'. The experiences of the participants in the theme 'Inductive process of moral distress development' were categorized into three categories: 'Melting into the faulty system', 'Power and the system as distress promotors', and 'Perceived unpleasant consequences'. Conclusion The results indicated that the frequency of moral distress in operating rooms and surgical units was at a moderate level and the distress intensity of nurses was at a moderately high level. The results indicated that in the investigated system, the "inductive moral process of distress development" was continuously understood by the participants. This process was influenced by systemic and individual factors. Weak assertiveness, conservative compromise, and desensitization to unprofessionalism as individual factors were effective in causing distress. Risk factors at the systemic level led nurses to melt into the faulty system and created adverse outcomes at the individual level. The lack of systemic support and the stabilization of mobbing by powerful system members had a negative impact on the individual factors of distress development. Also, these factors directly cause negative consequences.